The Impact of Russia’s Oil-Dominated Energy Economic Changes on the Exchange Rate of Russian Ruble – Chinese Renminbi - Maoguo Wu; Yue Yu (European Scientific Journal, ESJ, 2017)
Russia’s economic development has a close relation with China, due to geographical and historical reasons. This paper investigates whether the ruble – renminbi exchange rate changes accordingly when the pillar industry of Russia is drastically changing, and how the exchange rate changes and how it affects Russia’s economic development. In this paper, data of 7 variables spanning 122 months are selected based on related literature and availability of data. Regression analysis and empirical tests are carried out consequently. The results show that the energy price index represented by oil prices is negatively correlated with the exchange rate, and the explanatory power is as high as 41.1%. Following basic arbitrage methods and strategies, this paper verifies the feasibility of using arbitrage by comparing actual exchange rates with forecasted exchange rates. According to empirical results, problems witnessed in the process of ruble internationalization provides policy implications for China. China’s economy is utilized as an example to discuss the shortcomings of Russia’s economy. Related solutions are proposed.